1989
DOI: 10.1021/jm00121a024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological properties of a new series of cis-diammineplatinum(II) antitumor agents containing three nitrogen donors: cis-[Pt(NH3)2(N-donor) Cl]+

Abstract: A series of 32 cationic platinum(II) complexes of the form cis-[PtA2(Am)Cl]+, where A is a monodentate (NH3 or i-PrNH2) or A2 is a bidentate (ethylenediamine or 1,2-diaminocyclohexane) amine and Am is either a heterocyclic amine based on a pyridine, pyrimidine, purine, piperidine, or a saturated amine (RNH2) ligand, was prepared and screened against in vivo murine tumor models. Each compound was tested against Sarcoma 180 ascites (S180a) in mice, with 20 members of the series showing activity (ILS greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 6 publications
6
168
0
1
Order By: Relevance
“…The complex that gave the best results, far better than those of oxaliplatin, was cationic cis-diamminepyridinechloroplatinum(II), also referred to as cDPCP or pyriplatin (figure 1) [27]. The anti-cancer activity of this compound had been investigated previously in an animal model [28], but only a small number of follow-up studies on related compounds were performed [29]. In addition to significant organic character and cationic charge, pyriplatin is of interest because only one labile chloride ligand is present in the coordination sphere.…”
Section: Monofunctional Platinum Anti-cancer Agents (A) Pyriplatin: Rmentioning
confidence: 99%
“…The complex that gave the best results, far better than those of oxaliplatin, was cationic cis-diamminepyridinechloroplatinum(II), also referred to as cDPCP or pyriplatin (figure 1) [27]. The anti-cancer activity of this compound had been investigated previously in an animal model [28], but only a small number of follow-up studies on related compounds were performed [29]. In addition to significant organic character and cationic charge, pyriplatin is of interest because only one labile chloride ligand is present in the coordination sphere.…”
Section: Monofunctional Platinum Anti-cancer Agents (A) Pyriplatin: Rmentioning
confidence: 99%
“…This perturbation should influence the recognition and the repair of platinum-DNA adducts of 9 and 10 (compare Refs. [21] and [25]). …”
Section: Discussionmentioning
confidence: 98%
“…Likewise, the rule that monofunctional platinum(II) complexes, which contain 3 amine ligands and only one leaving group such as CI-, are inactive, has been disproved by Hollis et al [25]. The authors showed that such complexes inhibit the growth of several tumor models, inspite of their ability to react only with one nucleophilic center of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure used for synthesis is a modification of the methods of Lippert (Lippert et al, 1981) and Hollis (Hollis et al, 1989). 300 mg (1 mmol) of PtC12(C2HsN2) was dissolved in 20 ml of dimethylformamide (DMF).…”
Section: Methodsmentioning
confidence: 99%